2012
DOI: 10.5588/ijtld.11.0195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and associated factors among schoolchildren in rural South India

Abstract: In the present study, the prevalence of questionnaire-diagnosed asthma in the study group was 4.9%. Of the total number of schoolchildren with asthma, 17 (58.6%) were detected who had not been diagnosed previously. One third of the children with asthma had visited emergency departments in the last 12 months, indicative of poor asthma control. Another third suffered limitation of activity at home and or at school, which could indicate poor quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
4
16
1
Order By: Relevance
“…11,14,16,18,20,21 A significant association was found between history of allergy and asthma in the present study. Similar findings has been reported in the study by Dhabadi et al 6 History of cough without cold was strongly associated with asthma by both multivariate and univariate analysis, which shows similarities with other studies. 4,16,19 Other studies have also shown association of asthma with passive smoking, pets at home, environmental tobacco smoke, absence of smoke outlet 10,13,16,21 which has not been found statistically significant in this study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…11,14,16,18,20,21 A significant association was found between history of allergy and asthma in the present study. Similar findings has been reported in the study by Dhabadi et al 6 History of cough without cold was strongly associated with asthma by both multivariate and univariate analysis, which shows similarities with other studies. 4,16,19 Other studies have also shown association of asthma with passive smoking, pets at home, environmental tobacco smoke, absence of smoke outlet 10,13,16,21 which has not been found statistically significant in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Similar are the prevalence rates of asthma in school children in the study quoted by Chhabra et al 11 (15.7%) and in an another study by Mistry 17 ( 12.5%). Various studies on asthma in school children show variation in prevalence in rural and urban areas, 4,6,10,14,15,18,19 the prevalence being higher in urban children. This may be due to urban air pollution because of industries, automobiles, allergens etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is higher than some developing countries like Tibet area in China (1.1%), (35) India (4.9%) (36) and Taiwan (6%) (37). …”
Section: Discussionmentioning
confidence: 86%
“…In Japan prevalence of asthma was higher in boys (6%) than girls (4%) (38). In Turkey, the prevalence of asthma in boys (19.4%) is slightly higher than girls (16.2%) (34) similar to Nigeria, South Korea, and India (36,39,40). …”
Section: Discussionmentioning
confidence: 95%